Media sentiment on monetary policy: Determinants and relevance for inflation expectations. (June 2022) - Picault, Matthieu; Pinter, Julien; Renault, Thomas
Highlights: We construct a new indicator to capture media sentiment about the European Central Bank (ECB) monetary policy. We propose a methodology to dissociate the dissemination of official communications of the central bank from the media comments. Both press conference and inter-meeting communications of the President of the ECB significantly affect media sentiment. Daily changes in media sentiment have predictive power for financial market inflation expectation. Abstract: We construct a new indicator to capture media sentiment about the European Central Bank monetary policy and its relevant environment by analyzing 25, 000 articles from five major international newspapers. Using named entity recognition and part-of-speech tagging, we propose a methodology to dissociate the dissemination of official communications of the central bank from the media comments. The resulting (daily) index correlates with some (monthly) standard measures of economic sentiment but reveals idiosyncratic information on monetary policy. Analyzing the determinants of our index, we find that both press conference and inter-meeting communications of the President significantly affect media sentiment. We then show that, controlling for a large range of factors, daily changes in media sentiment have predictive power for financial market inflation expectations.